Heuristics legislation in the field of classified information as a function of training subjects of defense - Bereš, Paun J. (Vojnotehnički glasnik / Military Technical Courier, 2013)
Education on the protection of classified information should be the top priority when it comes to ensuring the protection of the vital interests of the state. Some information should not be made available to the public because it is mainly related to national security, and no one should question the need to protect this kind of data. This paper is intended for educators dealing with the protection of classified information, and especially to those who work with or come into contact with confidential information in order to inform them of our national system of protection of classified information and enable the implementation of the existing legislation applying the heuristic model of education. This article describes the legal regulations governing the protection of dataand shows mandatory standards and measures for the protection of classified information.